2010
DOI: 10.1007/s00018-010-0265-2
|View full text |Cite
|
Sign up to set email alerts
|

The corticotropin releasing factor system in cancer: expression and pathophysiological implications

Abstract: Malignant tumors express multiple factors that have some role in the regulating networks supporting their ectopic growth. Recently, increased interest has been developing in the expression and biological role of the neuropeptides and receptors of the corticotropin releasing factor (CRF) system, the principal neuroendocrine mediator of the stress response, especially in the light of several R&D programs for small molecule antagonists that could present some anticancer therapeutic benefit. In the present article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 110 publications
1
28
0
Order By: Relevance
“…It has been proposed that the CRF system plays an important role in various kinds of tumor (Kaprara et al 2010). Concerning CRF/Ucn effects on apoptosis, some researchers reported that CRF promoted the proliferation of tumor cells (Minas et al 2007) mainly via CRFR1, but others argued that CRF was favorable to apoptosis (Graziani et al 2002) and Ucn/Ucn2 promoted malignant cells growth via CRFR2 (Chatzaki et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the CRF system plays an important role in various kinds of tumor (Kaprara et al 2010). Concerning CRF/Ucn effects on apoptosis, some researchers reported that CRF promoted the proliferation of tumor cells (Minas et al 2007) mainly via CRFR1, but others argued that CRF was favorable to apoptosis (Graziani et al 2002) and Ucn/Ucn2 promoted malignant cells growth via CRFR2 (Chatzaki et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These peptides act through the corticotrophin releasing factor receptors 1 and 2 (CRF1/CRF2), two class II G protein coupled receptor (GPCR) 8 . Ligands and receptors regulated by stress and inflammation in the GI tract are expressed and secreted by many normal and cancer cells 9,10 . Animal models and in vitro experiments have shown that acute or chronic stress impairs the intestinal barrier by various mechanisms involving cytokines or kinases mediated regulation of cell junctions (for review 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Corticotropin-releasing hormone mediates endocrine responses to stress by activating the HPA axis as well as via direct actions in the periphery 10,11. Of note, the expression of CRH and its receptors has also been reported in several types of carcinoma 12,13. Specifically, Miceli14 reported CRH, CRHR1, and CRHR2 immunoreactivity in endometrial carcinoma.…”
mentioning
confidence: 99%
“…10,11 Of note, the expression of CRH and its receptors has also been reported in several types of carcinoma. 12,13 Specifically, Miceli 14 reported CRH, CRHR1, and CRHR2 immunoreactivity in endometrial carcinoma. Although stress is known to be a promoter of tumor growth, 15 it remains unclear whether CRH, CRHR1, or CRHR2 immunoreactivity in endometrial carcinoma is a risk factor for poor prognosis.…”
mentioning
confidence: 99%